Digitalization of Laundry Kocan Services and Promotion Through a Responsive Web-Based Information System - Elly Yunita; Eki Aryadi (Jurnal Armada Informatika, 2026)
Micro-scale laundry services require fast, transparent, and accessible information to remain competitive in an increasingly digital customer environment. Laundry Kocan previously relied on conventional information delivery, which limited customer access to business profiles, service prices, operating hours, and communication channels. This study aims to develop a responsive website-based information system as a service-information and digital-promotion medium for Laundry Kocan. A descriptive qualitative approach was employed. Primary data were obtained through field observation and an in-depth interview with the business owner, while secondary data consisted of price documents, promotional materials, and supporting literature. Data analysis followed reduction, display, conclusion drawing, and verification stages. System development comprised requirements analysis, interface design, HTML and CSS implementation supported by Bootstrap, and display testing on desktop and smartphone device categories. The implementation produced a landing page, business profile, digital price list, navigation, operating-hour information, and a responsive WhatsApp communication button. The source draft reports that the post-implementation indicator of new customers increased from 20% to 80%; because absolute counts, measurement period, and a comparison group were not documented, this figure is interpreted descriptively rather than as causal evidence. Overall, the website establishes a digital identity and improves the reach, consistency, and transparency of Laundry Kocan service information.